2020
DOI: 10.1021/acsami.0c14042
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Brushlike Slippery Coatings with Mechanically Robust, Self-Cleaning, and Icephobic Properties

Abstract: In this work, a facile strategy was proposed to prepare a series of brushlike thermoplastic polyurethane (TPU) coatings with mechanically robust, self-cleaning, and icephobic performance. Through a simple multicomponent click reaction of thiolactone with a diamine compound and mono-ethenyl-terminated polydimethylsiloxane (mono-ethenyl-PDMS), a diol with amide groups and flexible PDMS was synthesized, and a novel TPU could be obtained productively by a reaction of isocyanate and diol. The unique chain structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…Compared with previously reported values for bare Al surfaces (about 200−1600 kPa), 50−57 the ice-adhesion strength of our TMVS-capped PMHS film surface (20 kPa) was extremely small and in good agreement with previously reported values for PDMS-grafted surfaces (about 2.7−38.7 kPa). 28,33,36,37,41 In the scientific community, we recognize that icephobic surfaces usually exhibit the ice-adhesion strength of less than 100 kPa. 58 Although there was some variation in the data, the ice-adhesion strength remained almost unchanged (∼50 kPa) even after 20 cycles of testing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compared with previously reported values for bare Al surfaces (about 200−1600 kPa), 50−57 the ice-adhesion strength of our TMVS-capped PMHS film surface (20 kPa) was extremely small and in good agreement with previously reported values for PDMS-grafted surfaces (about 2.7−38.7 kPa). 28,33,36,37,41 In the scientific community, we recognize that icephobic surfaces usually exhibit the ice-adhesion strength of less than 100 kPa. 58 Although there was some variation in the data, the ice-adhesion strength remained almost unchanged (∼50 kPa) even after 20 cycles of testing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, a novel superhydrophobic composite with icephobicity has good prospects for development. Additionally, Tian et al 20 prepared a series of brush-like thermoplastic polyurethane coating materials and experimentally showed them to have good mechanical, hydrophobic, and icephobic properties. Pan et al 21 reported a novel triple-scale superhydrophobic surface with excellent anti-icing and deicing properties, as demonstrated by experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…As a passive method, anti-icing coatings have the advantages of low cost, small energy consumption, and environmental friendliness [2][3][4][5][6]. Because of low surface energy and elasticity, polydimethylsiloxane (PDMS) was widely used to prepare anti-icing coatings [4][5][6][7], and several coating surface modification approaches by PDMS were also applied [8][9][10].…”
Section: Introductionmentioning
confidence: 99%